Titanium dioxide (TiO2) nanoparticles filled poly(D,L lactid acid) (PDLLA) matrix composites for bone tissue engineering - Boccaccini, Aldo R.; et al. (Journal of Materials Science: Materials in Medicine, 2007)
Titanium dioxide (TiO2) nanoparticles were investigated for bone tissue engineering applications with regard to bioactivity and particle cytotoxicity. Composite films on the basis of poly(d,l lactid acid) (PDLLA) filled with 0, 5 and 30 wt% TiO2 nanoparticles were processed by solvent casting. Bioactivity, characterised by formation of hydroxyapatite (HA) on the materials surface, was investigated for both the free TiO2 nanoparticles and PDLLA/TiO2 composite films upon immersion in supersaturated simulated body fluid (1.5 SBF) for up to 3 weeks. Non-stoichiometric HA nanocrystals (ns-HA) with an average diameter of 40 nm were formed on the high content (30 wt% TiO2) composite films after 2 weeks of immersion in 1.5 SBF. For the pure PDLLA film and the low content composite films (5 wt% TiO2) trace amounts of ns-HA nanocrystals were apparent after 3 weeks. The TiO2 nanopowder alone showed no bioactivity. The effect of TiO2 nanoparticles (0.5-10,000 μg/mL) on MG-63 osteoblast-like cell metabolic activity was assessed by the MTT assay. TiO2 particle concentrations of up to 100 μg/mL had no significant effect on MG-63 cell viability. © 2007 Springer Science+Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.titani